2011
DOI: 10.1001/archoto.2011.158
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiation Therapy for High-Grade and/or Locally Advanced Major Salivary Gland Tumors

Abstract: Adjuvant RT is associated with improved survival for high-grade and/or locally advanced MMSGT based on analysis of this large, population-based database. Further prospective studies are warranted to examine the role of RT in the management of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 22 publications
5
70
0
2
Order By: Relevance
“…This survival effect was observed only in multivariate analysis after accounting for the other covariates. Interestingly, our result is numerically similar to the HR reported by Mahmood et al for major salivary gland tumors [17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This survival effect was observed only in multivariate analysis after accounting for the other covariates. Interestingly, our result is numerically similar to the HR reported by Mahmood et al for major salivary gland tumors [17].…”
Section: Discussionsupporting
confidence: 92%
“…Survival benefit for adjuvant RT was limited to the highest risk group with P(T|X) (0.67, 1). These results are in agreement with previously reported results for major salivary gland tumors [17]. We believe that such an approach allows for an unbiased way to estimate the patient's risk and can assist the treating physicians to decide whether adjuvant RT is warranted in individual cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The largest study completed regarding adjuvant RT for SGCs investigated 2170 patients from the Surveillance, Epidemiology, and End Results (SEER) registry. They found that postoperative adjuvant RT is associated with improved overall survival for high-risk disease (defined as poorly differentiated, undifferentiated, and/or locally advanced T3/4 or N+) 5 . Another SEER database study, however, investigated 1241 cases of parotid acinic cell carcinoma and found that adjuvant RT did not provide a tangible overall survival benefit in this population 6 .…”
Section: Introductionmentioning
confidence: 99%
“…MSGC encompass a cohort of histologies, of which the most common cancer is mucoepidermoid carcinoma, followed by adenoid cystic carcinomas and acinar cell neoplasms, and the most common site of involvement is the parotid gland. Because of the histological heterogeneity and biological behavior diversity, surgery-related issues and the role of radiation therapy were disordered [3, 4], and the 5-year overall survival (OS) rates of MSGC patient vary widely, ranging from 32% to 74% [5, 6]. In addition, since MSGC is rare, most reports of clinical prognostic factors, OS, and cancer-specific survival (CSS) are from small single-institution retrospective studies [58].…”
Section: Introductionmentioning
confidence: 99%